2001
DOI: 10.1007/s00210-001-0488-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by viozan of extravasation induced in rat trachea by capsaicin is mediated exclusively by β2-adrenoceptors

Abstract: The mechanism by which 2(3H)-benzothiazolone, 4-hydroxy-7-[2-[[2-[[3-(2-phenylethoxy)propyl]-sulphonyl]ethyl]amino]ethyl]-monohydrochloride (AR-C68397AA; viozan), a dual dopamine D2/beta2-adrenoceptor agonist which has shown promise in the treatment of chronic obstructive pulmonary disease (COPD), inhibits the extravasation of plasma protein induced by capsaicin in the tracheas of Brown Norway rats has been re-evaluated. Viozan (10-30 microg/kg given intratracheally; i.t.) inhibited dose-dependently the extrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“… Fozard et al . (2001) demonstrated an increased extravasation of plasma protein tagged with Evans Blue in the rat trachea (from the larynx to the bifurcation) 10 min after i.t.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Fozard et al . (2001) demonstrated an increased extravasation of plasma protein tagged with Evans Blue in the rat trachea (from the larynx to the bifurcation) 10 min after i.t.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, MRI signals following capsaicin administration were observed in lower parts of the lung that are associated with an increase of mucin concentration in BAL fluid. An explanation for the discrepancy between the current results and those of Fozard et al . (2001) could be the greater density of sensory nerves in upper airways compared to lower ones as demonstrated by Larson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These in vitro data seem to concur with in vivo data published which demonstrated that D 2 receptor agonists inhibit neuropeptide release from airway sensory nerves (Weyman‐Jones et al ., 1999) and that AR‐C68397AA and the D 2 receptor agonist ropinirole inhibit capsaicin evoked plasma extravasation into the airways in a sulpiride sensitive manner (Trevisani et al ., 2001). In some respects this data is in contrast to that published by Fozard et al . (2001) where inhibition by AR‐C68397AA of plasma extravasation in rat trachea induced by capsaicin was mediated exclusively by β 2 ‐adrenoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another group have shown an analogue of AR‐C68397AA, AR‐C65116AB, and ropinirole (Dopamine agonist, Eden et al ., 1991) to be effective in the same model and these effects could be blocked by the D 2 receptor antagonist, sulpiride (Trevisani et al ., 2001). In contrast, a recent study by Fozard et al . (2001), using a similar model, has shown the activity of AR‐C68397AA to be due solely to its activity on the β 2 adrenoreceptor and that a dopamine D 2 receptor agonist, quinagolide, was ineffective.…”
Section: Introductionmentioning
confidence: 99%